Acquisition and maintenance of pluripotency are influenced by fibroblast growth factor, leukemia inhibitory factor, and 2i in bovine-induced pluripotent stem cells - Botigelli, Ramon Cesar; Pieri, Naira Carolina Godoy; Bessi, Brendon William; Machado, Lucas Simões; Bridi, Alessandra; de Souza, Aline Fernanda; Recchia, Kaiana; Neto, Paulo Fantinato; Ross, Pablo Juan; Bressan, Fabiana Fernandes; Nogueira, Marcelo Fábio Gouveia (Frontiers in Cell and Developmental Biology, 2022)
Several opportunities for embryo development, stem cell maintenance, cell fate, and differentiation have emerged using induced pluripotent stem cells (iPSCs). However, the difficulty in comparing bovine iPSCs (biPSCs) with embryonic stem cells (ESCs) was a challenge for many years. Here, we reprogrammed fetal fibroblasts by transient expression of the four transcription factors (Oct4, Sox2, Klf4, and c-Myc, collectively termed “OSKM” factors) and cultured in iPSC medium, supplemented with bFGF, bFGF2i, leukemia inhibitory factor (LIF), or LIF2i, and then compared these biPSC lines with bESC to evaluate the pluripotent state. biPSC lines were generated in all experimental groups. Particularly, reprogrammed cells treated with bFGF were more efficient in promoting the acquisition of pluripotency. However, LIF2i treatment did not promote continuous self-renewal. biPSCs (line 2) labeled with GFP were injected into early embryos (day 4.5) to assess the potential to contribute to chimeric blastocysts. The biPSC lines show a pluripotency state and are differentiated into three embryonic layers. Moreover, biPSCs and bESCs labeled with GFP were able to contribute to chimeric blastocysts. Additionally, biPSCs have shown promising potential for contributing to chimeric blastocysts and for future studies.